Placement of a transjugular intrahepatic portosystemic shunt in addition to recanalization of acute and chronic portomesenteric vein occlusions – a retrospective evaluation. (October 2020) - Barbier, Charlotte Ebeling; Rorsman, Fredrik; Eriksson, Lars-Gunnar; Sangfelt, Per; Sheikhi, Reza; Vessby, Johan; Nyman, Rickard
Background: Portomesenteric vein thrombosis may be life-threatening due to bowel ischemia caused by venous stasis, or variceal bleeding caused by portal hypertension. Purpose: To evaluate the effectiveness and safety of recanalization combined with transjugular intrahepatic portosystemic shunt in acute and chronic portomesenteric vein thrombosis in patients with and without liver cirrhosis. Material and Methods: 21 consecutive patients (5 women, 16 men; mean 48 years) with portomesenteric vein thrombosis (8 acute, 13 chronic) treated at the Interventional Radiology department between March 2014 and September 2018 were retrospectively reviewed. The main portal vein was completely obliterated and the portomesenteric vein thrombosis extended into the superior mesenteric vein in all patients. The portomesenteric vein thromboses were recanalized transhepatically, a transjugular intrahepatic portosystemic shunt was inserted, thrombectomy was performed in acute portomesenteric vein thrombosis, and angioplasty with or without additional stenting was performed in chronic portomesenteric vein thrombosis. Results: Recanalization was successful in 8/8 patients (100%) with acute portomesenteric vein thrombosis, and in 11/13 patients (85%) with chronic portomesenteric vein thrombosis. In 12 patients, blood flow was restored in one session. Several sessions were more frequently needed in patients with acute portomesenteric vein thrombosis compared to those with chronic portomesenteric vein thrombosis ( p = 0.003). Re-occlusion occurred and was recanalized in 10/19 patients and was more frequent in patients with chronic ( n = 8/11) than on those with acute ( n = 2/8) portomesenteric vein thrombosis ( p = 0.04). Adverse events occurred in five patients. There was no 30-day mortality. Conclusion: Recanalization and insertion of a transjugular intrahepatic portosystemic shunt is safe and effective in patients with acute and chronic portomesenteric vein thrombosis with or without cirrhosis. Recanalization was more likely to stay patent in acute compared with chronic portomesenteric vein thrombosis.